Symmetric Dimethylarginine in Cats with Hypertrophic Cardiomyopathy and Diabetes Mellitus. (12th December 2017) - Langhorn, R.; Kieler, I.N.; Koch, J.; Christiansen, L.B.; Jessen, L.R.
Abstract : Background: Symmetric dimethylarginine (SDMA) has been increasingly used as a marker of early chronic kidney disease (CKD) in cats, but little is known about the influence of comorbidities on SDMA in this species. Hypothesis: Hypertrophic cardiomyopathy (HCM) and diabetes mellitus (DM), independently of CKD, are associated with changes in serum SDMA. Animals: Ninety‐four cats (17 with CKD, 40 with HCM, 17 with DM, and 20 healthy controls). Methods: Case‐control study. Clinical examination, echocardiography, ECG, blood pressure, CBC, biochemistry, thyroxine, and SDMA measurement were performed. Urinalysis was performed in controls and cats with CKD and DM. Analysis of variance was used to compare overall differences in the log‐transformed SDMA data among groups. A random forest algorithm was applied to explore which clinical and other factors influenced serum SDMA. Results: Median (range) serum SDMA for the renal group (positive control) was 19 (10–93) μg/dL, whereas for the control group (negative control), it was 10 (5–15) μg/dL. For the cardiac and diabetic groups, serum SDMA was 9 (4–24) μg/dL and 7 (3–11) μg/dL, respectively. The renal group had significantly higher SDMA concentrations and the diabetic group significantly lower SDMA concentrations compared to all other groups. Conclusions and Clinical Importance: Serum SDMA concentrations in cats with HCM were not significantly different from those of healthy control cats. Cats with DM, however, had significantly lower SDMA concentrations than controls, a finding that needs further investigation and should be kept in mind when evaluating renal function of cats with this endocrinopathy.